La política pública de inclusión de los jóvenes en el mercado laboral: estudio del programa mi primer empleo en la provincia de Loja (2010 – 2011) - Contento Armijos, Doris Alexandra (2017)
The determination of public problems and his agendamiento depends on the incidence of the different groups involved and the impact that generate before the eyes of the public administrators. The design of the policy, for its part, depends on a proper diagnosis which should draw on the information provided by those affected through participatory processes of analysis and reflection. These and other aspects are addressed in the present research work whose objective is to analyze the extent to which the design of public policy involved in the program My First Job, carried out by the Ministry of Labor, picked up the main elements of the problem of youth unemployment. In this research work is a both a quantitative and a qualitative analysis, in order to contrast the hypothesis that the design of the program My First Job does not recover the particularities of the problem.